TP53 Gain-of-Function Mutation is a Poor Prognostic Factor in High-Methylated Metastatic Colorectal Cancer - Wakayama, Shonosuke; Ouchi, Kota; Takahashi, Shin; Yamada, Yasuhide; Komatsu, Yoshito; Shimada, Ken; Yamaguchi, Tatsuro; Shirota, Hidekazu; Takahashi, Masanobu; Ishioka, Chikashi (Clinical colorectal cancer, 2023)
Neither TP53 mutation nor DNA methylation status has been established as a biomarker alone of metastatic colorectal cancer. We analyzed the association between TP53 mutation functional subtypes and genome-wide DNA methylation status (GWMS) as combined prognostic markers. Patient clinical data were obtained from the TRICOLORE study, a randomized phase III trial. The TP53 mutations were classified into wild-type, gain-of-function (GOF) mutations, and non-gain-of-function (non-GOF) mutations. GWMS of the tumor tissues classified them into high-methylated colorectal cancer (HMCC) and low-methylated colorectal cancer (LMCC). Overall survival (OS) was compared based on these subgroups. Of the 209 patients, 60 (28.7%) were HMCC and 149 (71.3%) were LMCC, 35 (16.7%) were TP53 wild-type and 174 (83.3%) were TP53 mutants including 79 (45.4%) GOF mutations and 95 (54.6%) non-GOF mutations. The OS of the HMCC group was shorter than that of the LMCC group (median 25.3 vs. 40.3 months, P < .001, hazard ratio 1.87) in the total cohort. The combined subgroup analyses of GWMS and TP53 mutation subtypes showed that the HMCC/GOF group had significantly shorter OS than the HMCC/non-GOF group, the LMCC/GOF group, and the LMCC/non-GOF group (median 17.7; 35.3, 40.3, and 41.2 months, P = .007, P < .001, and P < .001, respectively), regardless of the primary tumor location. By the multivariate analysis, only HMCC (P = .009) was a poor prognostic factor in the GOF mutation group. TP53 GOF with HMCC is a newly identified poorest prognostic molecular subset in metastatic colorectal cancer. Neither TP53 mutation nor genome-wide DNA methylation status has been established as a biomarker of metastatic colorectal cancer. These were evaluated as prognostic factors using data of 209 patients in a phase III clinical trial. Multivariate analysis revealed that TP53 GOF with HMCC is a newly identified poorest prognostic molecular subset in metastatic colorectal cancer.